Investigation of porcupine bezoar extract (Hystrix Brachyuran) on hela cell combined with electroporation method - Azizulkarim, Azra Hazwanie (2019)
Electroporation (EP) is a technique whereby the cell membrane is exposed to increase the intensity of electric field pulses that can lead to a variety of biophysical and biochemical responses. It is a molecular biology technique that stimulates pores through cell membrane, to increase the permeability of the cell, allowing chemicals, and drugs or Deoxyribonucleic acid (DNA) to be introduced into the cell. In this research, the HeLa cell behavior was investigated via EP. The purpose of this study is to investigate the best parameter of EP to be applied on HeLa cell treated with the best concentration of PBE which was 80.0ug/ml. Thus, the experiment is conducted for 48 hours and is initiated by identifying the best parameter for EP process. The range of electric field used is commenced between 100V/cm and 500V/cm with the increment of 100 V/cm interval sand for the pulse duration from 100μs, 500μs, 1ms, 2ms and 5ms. Based on the parameter used, the best result obtained is when the parameter was set to 500 V/cm for the electric field and 100μs for pulse duration, where it inhibits the lowest proliferation rate percentage of HeLa cell. For the natural resource compound or extract which is available in Malaysia Porcupine Bezoar (Hystrix Brachyuran) were used. This extract has the potential as an anti-proliferation agent, which is useful in anti-cancer application. The experiment suggests that the best concentration for Porcupine Bezoar Extract (PBE) was at 80.0ug/ml. This combined method of EP and PBE revealed the process inhibited the proliferation of HeLa cell to 8.48%. In comparison to the study without this combined technique of EP and PBE, the inhibition process reached 55.35%.The study has successfully demonstrated the contribution towards a new method for anti-cancer treatment due to its minimal side effects compared to other conservative methods such as Electrochemotherapy (ECT).